Design, Synthesis and Evaluation of the Biological Activities of Some New Carbohydrazide and Urea Derivatives - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (TURKISH PHARMACISTS ASSOC, 2018)
Objectives: Urea and carbohydrazide derivatives are important compounds exhibiting cytotoxic activities. In this study, a series of new urea and carbohydrazide derivatives containing an pyridine ring were synthesized and evaluated for cytotoxic activity. Materials and Methods: The proposed structures of the synthesized compounds were confirmed using elemental analysis, IR, and H-1-NMR spectroscopic techniques. The cytotoxic potencies of synthesized compounds were determined using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay (MTT) on BRCA mutant-carrying HCC1937 and Capan-1 cell lines, as well as on MCF7, HeLa, and MRC5 cells. Results: 3a, 3b, 3c and 3d showed cytotoxic activity against all cancer cell lines. Conclusion: Our data indicate that compounds 3a-d are more selective to cancer cells compared with nontumoral fibroblasts; however, these compounds are not more potent on HR defective cells with BRCA mutants.
Keywords: Carbohydrazide; urea; cytotoxic activity; HYDRAZONE